Social responsibility and subjective well-being of volunteers for COVID-19: The mediating role of job involvement - Wu, Chao; Cheng, Sizhe; Zhang, Yinjuan; Yan, Jiaran; He, Chunyan; Sa, Zhen; Wu, Jing; Lin, Yawei; Heng, Chunni; Su, Xiangni; Lang, Hongjuan (Frontiers in Psychology, 2022)
Aim: Our study aimed to investigate the effect of social responsibility on the subjective well-being of volunteers for COVID-19 and to examine the mediating role of job involvement in this relationship. Background: Nowadays, more and more people join volunteer service activities. As we all know, volunteer work contributes to society without any return. Volunteers often have a strong sense of social responsibility and reap subjective well-being in their dedication. Although research shows that social responsibility will drive them to participate in volunteer work actively, it’s less clear whether job involvement will impact their subjective well-being. Methods: The data were collected in the precaution zone in Shanghai, China, from April to May 2022. A sample of 302 volunteers for COVID-19 completed the social responsibility scale, subjective well-being scale and job involvement scale in the form of an electronic questionnaire on their mobile phones. A structural equation model was adopted to verify the research hypotheses. Results: Social responsibility was significantly and positively related to volunteers’ subjective well-being and job involvement (p< .05). Job involvement fully mediates the relationship between volunteers’ social responsibility and subjective well-being. Conclusion: Social responsibility is critical to predicting volunteers’ subjective well-being. Job involvement plays an intervening mechanism in explaining how social responsibility promotes volunteers’ subjective well-being.